Deep Venous Thrombosis of the Leg, Associated with Agenesis of the Infrarenal Inferior Vena Cava and Hypoplastic Left Kidney (KILT Syndrome) in a 14-Year-Old Child - Sakshi Bami; Yarelis Vazquez; Valeriy Chorny; Rachelle Goldfisher; John Amodio (Hindawi Limited, 2015)
Agenesis of the inferior vena cava (IVC) is a rare anomaly which can be identified as incidental finding or can be associated with iliofemoral vein thrombosis. IVC agenesis has a known association with renal anomalies which are mainly confined to the right kidney. We describe a case of a 14-year-old male who presented with left leg swelling and pain. Ultrasonography confirmed the presence of left leg deep vein thrombosis (DVT). No underlying hematologic risk factors were identified. A CT scan was obtained which demonstrated absent infrarenal IVC and extensive thrombosis in the left deep venous system and development of collateral venous flow into the azygous/hemiazygous system, with extension of thrombus into paraspinal collaterals. An additional finding in the patient was an atrophic left kidney and stenosis of an accessory left renal artery. Agenesis of the IVC should be considered in a young patient presenting with lower extremity DVT, especially in patients with no risk factors for thrombosis. As agenesis of the IVC cannot be corrected, one should be aware that there is a lifelong risk of lower extremity DVT.